Sistem Komunikasi Radio Terpadu Masyarakat Mitra Polhut dan Masyarakat Peduli Api di Kawasan Gunung Merapi - Samuel Kristiyana; Diky Siswanto; Prastyono Eko Pambudi (Jurnal Pemberdayaan Umat, 2022)
Purpose: to find out the Integrated Radio Communication System potential volunteers from the community who are members of the MPP and MPA to increase their understanding of mastery of radio communication tools, ethics, and coded communication and to follow the frequency regulations set by the Ministry of Communications and Information Technology. Methode: The community service method uses an Integrated Radio Communication System workshop and training for people who are members of the MPP and MPA on how to set up radio communication tools, using two-meter band radio communication procedures, communication ethics, and mastery of communication languages. Result: Design and installation of radio repeater Integrated Radio Communication System Workshop resulted in an understanding of the SKRT system and improved MPP and MPA capabilities. Mastery of communication tools, ethics, communication code language, and following frequency regulations set by the government. Limitations: By planning and implementing the SKRT and preparing volunteers from the community, MPP and MPA will support the main tasks and functions of the Taman Nasional Gunung Merapi for the protection and security and handling of the Mount Merapi eruption disaster. Research Contribution: Carrying out the implementation, in this case, is the Taman Nasional Gunung Merapi to plan and implement the SKRT and prepare the potential of the community to take joint responsibility for the conservation, protection, and security, and disaster response of Mount Merapi.